Social aspects of the transition to farming in the Balkans - Dušan Mihailović (Documenta Praehistorica, 2007)
The Neolithization of the Balkans could be considered as a very complex social phenomenon. In this work we study the causes for the cultural and social integration of hunter-gatherer communities in the Late Glacial and Early Holocene, social networks and contacts in the Iron Gates Mesolithic, and also factors having an impact on the spread of the Neolithic in the Balkans. It has been perceived that the evolution of culture in the Balkans was simultaneously influenced by internal and external factors, and this contributed to the very rapid acceptance of Neolithic values and the Neo- lithic way of life in the period from 6500 to 6200 calBC.